The characteristics of railway service disruption: implications for disruption management - Golightly, David; Dadashi, Nastaran (Taylor & Francis, 2016)
Rail disruption management is central to operational continuity and customer satisfaction. Disruption is not a unitary phenomenon - it varies by time, cause, location and complexity of coordination. Effective, user-centred technology for rail disruption must reflect this variety. A repertory grid study was conducted to elicit disruption characteristics. Construct elicitation with a group of experts (n=7) captured 26 characteristics relevant to rail disruption. A larger group of operational staff (n=28) rated 10 types of rail incident against the 26 characteristics. The results revealed distinctions such as business impact and public perception, and the importance of management of the disruption over initial detection. There were clear differences between those events that stop the traffic, as opposed to those that only slow the traffic. The results also demonstrate the utility of repertory grid for capturing the characteristics of complex work domains.